Development of E-module Based on Guided Inquiry in Chemical Bonding Topic for Class X Student Learning Materials - Pawestri, Nur Arneta; Erlina*, Erlina; Harun, Andi Ifriany; Sahputra, Rachmat; Lestari, Ira (Universitas Syiah Kuala, 2023)
The lack of teaching materials that are able to explain the formation of chemical bonds causes students difficulties in learning. Therefore, this study focused on developing guided inquiry-based e-module of chemical bonding. This study aims to determine the feasibility and students response to guided inquiry-based e-module of chemical bonding. This study employs research and development (RD) using ADDIE model which is limited to development stage. The due diligence was carried out by material, media and language experts. The respondents involved were 31 students of class XI MAN 2 Pontianak. The research instruments were the feasibility sheets, media, language, and response questionnaires. The results of the feasibility of e-module test is k=1 (very high validity) and student response tests k=0.85 (very interesting). Those findings indicate that the E-module is very feasible to use